(untitled) (HEALTH CARE: JURNAL KESEHATAN, 2024)
The Chronic Disease Management Program (Prolanis) is a program specifically for the management of Diabetes Mellitus and Hypertension. This program aims to ensure that participants can achieve an optimal quality of life so that they can prevent disease complications, with cost-effective and efficient health services. Based on the number of Diabetes Mellitus sufferers at the Merdeka Health Center in Palembang City in 2022, it will be 655 people, in 2023 it will increase to 755 people, but of that number, only 266 people are prolanis participants. This study aims to determine the factors associated with the use of Prolanis in Diabetes Mellitus sufferers at the Merdeka Community Health Center. Conducted in June-July 2024. This research is quantitative with a cross sectional design, the population in this study is all Diabetes Mellitus sufferers who live in the working area of ​​the Merdeka Health Center in 2024 totaling 268 people. With a sampling technique using proportional random sampling. Data collection and retrieval uses a questionnaire. The results of the statistical test analysis used the Chi-Square statistical test and logistic regression where the results showed that there was a significant relationship (p value < 0.05) for the variable knowledge about Prolanis (0.000) on the use of Prolanis at the Merdeka Community Health Center. There is no relationship between the variables age (0.489), gender (0.432), education (0.843), employment (0.209), family support (0.367) on the use of Prolanis at the Merdeka Community Health Center. It is recommended for health workers to increase community health center program activities in the form of counseling or assistance regarding the types of activities and their schedules, the benefits and objectives of Prolanis, regarding the prevention or management of Diabetes Mellitus.